2014
DOI: 10.1097/eja.0000000000000093
|View full text |Cite
|
Sign up to set email alerts
|

The effect of perioperative administration of glucocorticoids on pulmonary complications after transthoracic oesophagectomy

Abstract: In this meta-analysis, perioperative administration of glucocorticoid did not affect the risk of pulmonary complications after transthoracic oesophagectomy, nor did it cause adverse effects. A subgroup analysis showed that a weight-dependent dose of methylprednisolone 10 to 30 mg kg within 30 min preoperatively might be the most promising dosing regimen for further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 32 publications
1
32
0
Order By: Relevance
“…All operations in this study were performed under general anesthesia with epidural analgesia. For standard prophylaxis against lung dysfunction following esophagectomy, methyl-prednisolone (125 mg/body) 8,17) was given at the beginning of the operation 16) and every 24 hours after the initial administration for 4 days (including the operative day). Postoperatively, all patients underwent mechanical ventilation and were cared for in the intensive care unit (ICU).…”
Section: Perioperative Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…All operations in this study were performed under general anesthesia with epidural analgesia. For standard prophylaxis against lung dysfunction following esophagectomy, methyl-prednisolone (125 mg/body) 8,17) was given at the beginning of the operation 16) and every 24 hours after the initial administration for 4 days (including the operative day). Postoperatively, all patients underwent mechanical ventilation and were cared for in the intensive care unit (ICU).…”
Section: Perioperative Managementmentioning
confidence: 99%
“…5) Oxidative stress and inflammation are believed to play crucial roles in the pathogenesis of impaired oxygenation. 5,6) To improve oxygenation, drugs such as elastase inhibitor 7) or corticosteroids 8,9) are given, but their therapeutic effect has not been confirmed. 7,8,10) Combination therapy with corticosteroids, ascorbic acid, and thiamine has a prominent therapeutic effect on oxidative stress and inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mortality exceeds 50% when ARDS occurs [2]. ARDS, which is not related to pneumonia or anastomotic leak, results from a massive release of inflammatory cytokines during esophagectomy due to the radical dissection of gastro-enteral organs [3][4][5] and one lung ventilation (OLV) which increases inflammatory cytokines in both dependent and non-dependent lungs [6]. Excessive neutrophils recruited in response to the pro-inflammatory cytokines increase pulmonary vascular permeability [7].…”
Section: Introductionmentioning
confidence: 99%
“…Preventive administration of corticosteroid was reported to reduce ARDS after esophagectomy by inhibiting inflammatory responses [9,10]. However, there are also studies that showed no beneficial effect of corticosteroid on ARDS [3,11]. Moreover, there are concerns that corticosteroid can impair the healing process of surgical wounds and produce leakage of the anastomosis site by antiinflammatory effects and antagonistic effects on growth factors [12][13][14].…”
Section: Introductionmentioning
confidence: 99%